IMPLEMENTASI PERATURAN BUPATI NO 4 TAHUN 2018 TENTANG PENGANGKATAN DAN PEMBERHENTIAN PERANGKAT DESA KECAMATAN AMUNTAI SELATANÂ KABUPATEN HULU SUNGAI UTARA: (STUDI DESA JUMBA DAN HARUSAN TELAGA) - N Nasripani (STIA Bina Banua Banjarmasin, 2021)
The village is a government organization that politically has the authority to manage and regulate citizens or groups. According to Law No. 6 of 2014, village can be interpreted as a legal community unit that has territorial boundaries, the village also has a government that enforces the regulations so that the village can develop properly, also in the Regent Regulation No.4 of 2018 concerning Organizational Structure and Work Procedures Village Administration and the Appointment of Village Officials. In this case the objective of the implementation of this Regent Regulation can be carried out properly. This research uses a qualitative approach with a qualitative descriptive type. The data collection techniques used were interviews, observation, and documentation. Sources of data were taken from a sample (purposive side) totaling 10 people. After the data has been collected, it is analyzed using techniques including reduction, data presentation, and conclusion drawing. The results of this study indicate that the implementation of Regent Regulation No. 4 of 2018 concerning the Appointment and Dismissal of Village Apparatus in Amuntai Selatan District Hulu Sungai Utara Regency (Case Studies in Jumba and Harusan Telaga Villages) has been running quite well, but there are still some inhibiting factors in This Regent Regulation, namely (1) There is still a chance for the acceptance of village officials using the kinship and family system (Desa Jumba). (2) The lack of socialization of the village government with the community in the Regent Regulation in appointing and dismissing village officials, so that the community still does not know about regulations (Harusan Telaga Village). While the driving factor in Regent Regulation No. 4 of 2018 is (1) The number of community candidates who registered in the appointment of village officials (Jumba Village). (2) With the implementation of the Regent Regulation, the appointment of village officials can be carried out properly without any fraud (Desa Jumba and Harusan Tealaga) In order for the implementation of Regent Regulation No.4 of 2018 concerning the Appointments and Dismissal of Village Apparatus in Amuntai Selatan Subdistrict, this regulation should be socialized and implemented in the village so that the village can develop more in the appointment and dismissal of village officials as stipulated in the regulations , so that fraud in the appointment and dismissal of village officials does not occur. Keywords : Implementation, appointment and dismissal of village officials